Analisis Rasio Profitabilitas, Rasio Likuiditas, dan Rasio Solvabilitas dalam Menilai Kinerja Keuangan pada PT Bank Mandiri (Persero) Tbk Tahun 2019-2024 - Winanti, Winanti; Firayanti, Yuni; Mahardhika, Tubagus (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2025)
This study aims to analyze the financial performance of PT Bank Mandiri (Persero) Tbk during the period 2019 to 2024 using financial ratios as measurement tools, namely Net Profit Margin (NPM), Return on Assets (ROA), Return on Equity (ROE), Current Ratio, Cash Ratio, Debt to Asset Ratio (DAR), and Debt to Equity Ratio (DER). The research method employed is descriptive quantitative with secondary data obtained from the annual financial statements of PT Bank Mandiri (Persero) Tbk. The results of the analysis show that NPM experienced fluctuations, with the highest value recorded in 2023 at 61.27% and the lowest in 2020 at 30.41%. ROA reached its peak in 2023 at 2.76% and the lowest in 2020 at 1.23%. ROE also showed a similar pattern, with the highest value in 2023 at 20.88% and the lowest in 2020 at 9.10%. The Current Ratio was at its highest in 2019 at 248.63% and dropped to its lowest in 2022 at 198.21%. The Cash Ratio recorded its peak in 2022 at 18.14%, and its lowest in 2020 at 14.90%. DAR demonstrated stability, with the highest value in 2020 at 80.55% and the lowest in 2023 at 76.37%. Meanwhile, DER reached its peak in 2022 at 612.14% and its lowest in 2019 at 490.71%.